The law governing parental relationships with children in Iranian and British law - Mohammad, Abasat Pour; Mehr, Naser Shayan (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Childhood is one of the most important and effective periods of life, in addition to paying attention to the child's physical and educational care, it should be socially and legally protected by the legislator, In this regard, how to define the responsibility of the parents and how they behave with the child and their guardianship, the citizenship and responsibility of supervisors, and the transfer of the child or their parents from one country to another, and also in terms of the interests and interests of children that the legislator must regulate in drafting the rules. This paper seeks to examine the rules of conflict resolution for children and their parents in Iranian and British law.